Healthy Aging: American Geriatrics Society White Paper Executive Summary. Issue 1 (1st November 2018) - Friedman, Susan M.; Mulhausen, Paul; Cleveland, Maryjo L.; Coll, Patrick P.; Daniel, Kathryn M.; Hayward, Arthur D.; Shah, Krupa; Skudlarska, Beata; White, Heidi K.
Abstract : In July 2015, the Journal of the American Geriatrics Society published a manuscript titled, "Failing to Focus on Healthy Aging: A Frailty of Our Discipline?" In response, the American Geriatrics Society (AGS) Clinical Practice and Models of Care Committee and Public Education Committee developed a white paper calling on the AGS and its members to play a more active role in promoting healthy aging. The executive summary presented here summarizes the recommendations from that white paper. The full version is published online atGeriatricsCareOnline.org . Life expectancy has increased dramatically over the last century. Longer life provides opportunity for personal fulfillment and contributions to community but is often associated with illness, discomfort, disability, and dependency at the end of life. Geriatrics has focused on optimizing function and quality of life as we age and reducing morbidity and frailty, but there is evidence of earlier onset of chronic disease that is likely to affect the health of future generations of older adults. The AGS is committed to promoting the health, independence, and engagement of all older adults as they age. Geriatrics as an interprofessional specialty is well positioned to promote healthy aging. We draw from decades of accumulated knowledge, skills, and experience in areas that are central to geriatric medicine, including expertise in complexity and the biopsychosocial model; attention to function and quality of life; the ability to provide culturally competent, person‐centered care; the ability to assess people's preferences and values; and understanding the importance of systems in optimizing outcomes.J Am Geriatr Soc 67:17–20, 2019.